Driving factors for runoff decline in the Upper Hanjiang basin, a major water source for the South-to-North Water Diversion Project in China - S. Zhang; D. Yang; X. Xu (Proceedings of the International Association of Hydrological Sciences, 2015)
With dramatic changes in climate and land-cover patterns around the world, it is of great significance to evaluate the corresponding influence on runoff change as water resources have become a strategic resource. We analysed the runoff change driven by landscape change and climate variation in Hanjiang River basin, which is the water source area of the central route of the South-to-North Water Diversion Project in China. Results show that the runoff decreased greatly from 1960 to 2012 in all the six selected sub-catchments. Attribution analysis results show that reduction of precipitation contributed to the catchment runoff decrease by 39.5–64.9% and landscape change, represented by increase of the parameter in the mathematical Budyko function contributed to the runoff decrease by 34.4–63.3%, while potential evapotranspiration change had a slightly negative contribution. In addition, the contribution is spatially variable from downstream to upstream. We conclude with a qualitative description about how water availability changes under changing landscape and climate conditions, and focus on the impact of vegetation cover change.